KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI HUTAN LARANGAN ADAT GHIMBO POTAI KABUPATEN KAMPAR PROVINSI RIAU - Pretti Sepsi Nola; Defri Yoza; M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Indonesia is a country that has abundant natural resources. The use of medicinal plants in Indonesia has started from the time of the ancestors of the Indonesia nation. Where the community has a traditional medical knowledge system using a diversity of plants around them that has been used for generations. The purpose of this study was to determine the composition of plant species and diversity of medicinal plant species that exist in the Ghimbo Potai customary prohibition forest in Kampar regency, Riau province. The research was carried out in the Ghimbo Potai customary prohibition forest area in Kampar regency, Riau province. This study used a purposive sampling method using the path system and the sampling intensity used was 2.5% or 1.75 ha from the total area of the study. The composition of plant species obtained were as many as 47 species with 26 families, while the types of vegetation that were potential as medicinal plants were 19 species with 14 families. The species diversity values obtained indicate that medicinal plants in both observation lines in Ghimbo Potai customary prohibition forest are classified as moderate or quite good with a value of 1 ≤ H’ < 3. Keywords : Families, medicinal plant, species diversity